The mobile phone as a tool for the profile of the new journalist - Andueza López, María Belén; Pérez Arozamena, Rosa (Historia y Comunicación Social, 2014)
Teaching a subject called Informational Technologies Workshop, by teachers, requires a constant innovation and alertness to the technological advances that affect journalism. Under this premise, we decided to conduct an experiment called Imagination to power so that students used their mobiles as a tool for recording pieces of information. If we live in the Internet Age, teach from the Internet Age.
Keywords: TIC; Teaching; Innovation; Forms; Mobile phones.º